The Role of Feral Goats in Maintaining Firebreaks by Using Attractants - Pareja, Javier (2020)
The threat of large forest fires is increasing, and the main causes are the depopulation of rural areas, along with the effects of climate change. To counter this threat in recent decades, there have been numerous proposals and actions aimed at promoting grazing in the forest as a tool for controlling biomass fuel. However, the continued disappearance of traditional herds makes this activity difficult. Rural depopulation has also meant that domestic species become feral, being habitual in the case of goats. Currently, little is known about the role that feral goats can play in the fight against forest fires. In this work, an analysis is made on the effect of feral goats on the control of the vegetation in firebreak areas. Furthermore, the effect of attractants, such as water, salt, or food, on goat behavior is also studied. The study was carried out on the island of Mallorca, where a population of feral goats occupies the mountain areas, and where it is common for them to graze on the network of firebreaks. The results showed that these areas in themselves exert an attractive effect with respect to the neighboring forest, and that the herbaceous biomass is reduced. This effect was enhanced with the implementation of water and salt points, although only in certain periods of the year. In general, it was possible to reduce the phytovolume of many species without affecting biodiversity in the short or medium term. Therefore, strategic management of feral animals, aimed at firebreak areas, could contribute not only to reducing the risk of fires and, consequently, to the mitigation of climate change, but also to attracting these animals to the forests, thus avoiding their dispersion to conflictive places such as roads, residences, agricultural fields, and gardens.